Geographic and Ethnic Inequalities in Diabetes-Related Amputations - Bellia, Alfonso; Meloni, Marco; Andreadi, Aikaterini; Uccioli, Luigi; Lauro, Davide (Frontiers in Clinical Diabetes and Healthcare, 2022)
Individuals with diabetes mellitus are at increasing risk for major lower-extremity amputations (LEAs). Poor quality of life and remarkable disabilities are associated with LEAs, determining a high economic burden for the healthcare systems. Reducing LEAs is therefore a primary marker of quality of care of the diabetic foot. At global level, between-countries comparisons of LEAs rates are basically hampered by differences in criteria used for data collection and analysis among studies. Significant variability in amputation rates exists between geographic areas, and also within specific regions of a country. Overall 5-year mortality rate after major amputations is reported to vary substantially across countries, from 50 to 80%. The odds of LEAs are substantially higher for Black, Native American and Hispanic ethnicities compared with White groups, with similar figures observed in the economically disadvantaged areas compared to more developed ones. Such discrepancies may reflect differences in diabetes prevalence as well as in financial resources, health-care system organization and management strategies of patients with diabetic foot ulcers. Looking at the experience of countries with lower rates of hospitalization and LEAs worldwide, a number of initiatives should be introduced to overcome these barriers. These include education and prevention programs for the early detection of diabetic foot at primary care levels, and the multidisciplinary team approach with established expertise in the treatment of the more advanced stage of disease. Such a coordinated system of support for both patients and physicians is highly required to reduce inequalities in the odd of diabetes-related amputations worldwide.